Let's simplify the expression step by step:
The expression is given as:
\[ (16 - 12)^2 + 5(8 + 2^2) \cdot 5^3 - (1 + 4)^2 \]
-
Calculate \( (16 - 12)^2 \): \[ 16 - 12 = 4 \implies (4)^2 = 16 \]
-
Calculate \( (1 + 4)^2 \): \[ 1 + 4 = 5 \implies (5)^2 = 25 \]
-
Calculate \( 2^2 \): \[ 2^2 = 4 \]
-
Now calculate \( 8 + 2^2 \): \[ 8 + 4 = 12 \]
-
Then calculate \( 5(12) \): \[ 5 \cdot 12 = 60 \]
-
Now calculate \( 5^3 \): \[ 5^3 = 125 \]
-
Now calculate \( 5(12) \cdot 5^3 \): \[ 60 \cdot 125 = 7500 \]
-
Now substitute everything back into the expression: \[ 16 + 7500 - 25 \]
-
Calculate \( 16 - 25 \): \[ 16 - 25 = -9 \]
-
Now, add \( 7500 \): \[ -9 + 7500 = 7491 \]
So, the simplified numerator of the expression is \( 7491 \).
Given the provided options, it looks like there is no matching answer in the choices:
- \( 76 \)
- \( 100 \)
- \( 54 \)
- \( 4^2 + 60 \)
Thus, none of the choices are correct based on the simplification performed.